NEW RESULTS ON THE RESISTIVITY STRUCTURE OF MERAPI VOLCANO (INDONESIA), DERIVED FROM THREE-DIMENSIONAL RESTRICTED INVERSION OF LONG-OFFSET TRANSIENT ELECTROMAGNETIC DATA - Commer M.; Helwig S.L.; Tezkan B.; Hördt A.; Scholl C. (My University, 2006)
Three long-offset transient electromagnetic (LOTEM) surveys were carried out at the active volcano Merapi in Central Java (Indonesia) during the years 1998, 2000 and 2001. The measurements focused on the general resistivity structure of the volcanic edifice at depths of 0.5-2 km and the further investigation of a southside anomaly. The measurements were insufficient for a full 3-D inversion scheme, which could enable the imaging of finely discretized resistivity distributions. Therefore, a stable, damped least-squares joint-inversion approach is used to optimize 3-D models with a limited number of parameters. The models feature the realistic simulation of topography, a layered background structure, and additional coarse 3-D blocks representing conductivity anomalies. 28 LOTEM transients, comprising both horizontal and vertical components of the magnetic induction time derivative, were analysed. In view of the few unknowns, we were able to achieve reasonable data fits. The inversion results indicate an upwelling conductor below the summit, suggesting hydrothermal activity in the central volcanic complex. A shallow conductor due to a magma-filled chamber, at depths down to 1 km below the summit, suggested by earlier seismic studies, is not indicated by the inversion results. In conjunction with an anomalous-density model, derived from a recent gravity study, our inversion results provide information about the southern geological structure resulting from a major sector collapse during the Middle Merapi period, approximately 14000 to 2200 yr BP. The density model allows to assess a porosity range and thus an estimated vertical salinity profile to explain the high conductivities on a larger scale, extending beyond the foothills of the volcano. © 2006 RAS.
Keywords: 3-D LEAST SQUARES INVERSION; MERAPI VOLCANO; TRANSIENT ELECTROMAGNETIC FIELDS